The path toward an HIV‐1 vaccine. Issue 5 (September 2017) - Garces, Fernando
Abstract : Abstract : HIV is responsible for millions of deaths around the world and in the absence of available treatment capable of a cure, only the vaccine can offer protection against this virus. However, and after three decades of research, such a vaccine remains elusive. Here, I attempt to explain the major challenges on the development of an anti‐HIV immunogen, and how the three‐dimensional pictures of antibodies interacting with this virus can guide us to the design of a successful vaccine.